The effect of brace treatment on pulmonary functions in adolescent idiopathic scoliosis: An 8-month follow-up study - Yurt, Yasin; Yatar, Ilker; Malkoc, Mehtap; Yakut, Yavuz; Mihcioglu, Serpil; Koltak, Cansu (Ios Press, 2021)
BACKGROUND: The instant effect of a brace on pulmonary functions of patients with adolescent idiopathic scoliosis (AIS) is known. However, the permanent effects of its regular use are still unclear. OBJECTIVE: This study aimed to determine whether a brace in patients with AIS had a permanent effect on respiratory functions. METHODS: Fifteen patients with a mean age of 13.2 +/- 1.6 years, and a major Cobb angle of 25.8 degrees +/- 7.7 degrees participated in this study. Lung volumes and respiratory muscle strength were measured with and without thoracolumbosacral brace, at the end of first month and follow-up period after the patients started using the brace for 23 hours daily. RESULTS: When the brace was on, the forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), ratio of FEV1/FVC, peak expiratory flow, and forced expiratory flow between 25% and 75% of vital capacity values were found to be lower at both first month and follow-up. After the follow-up, the measurement results did not differ from the results of the first month. CONCLUSIONS: The brace had a momentary restrictive effect on patients with AIS. However, it did not cause a permanent change in pulmonary functions after the 8-month follow-up.
Keywords: Scoliosis; braces; pulmonary function test; respiratory muscle